The Impact of Energy Loss Index and Body Mass Index on Prosthesis Patient Mismatch. Issue 4 (4th July 2021) - Hite, Aimee; Karabon, Patrick; Mando, Ramy; Hanzel, George; Shannon, Francis; Abbas, Amr E.
ABSTRACT: Background: Prosthesis-patient mismatch (PPM) occurs following transcatheter aortic valve replacement (TAVR) with conflicting data on prognosis. It is considered present when the echocardiographic-derived indexed aortic valve area (iAVA) is <0.85 cm 2 /m 2 and severe when <0.65 cm 2 /m 2 . Pressure recovery, not accounted for in the continuity equation, leads to an overestimation of the incidence and severity of PPM, but can be corrected for using the energy loss index (ELI). This study seeks to determine the impact of pressure recovery on the incidence and severity of PPM by ELI. Methods: This retrospective study included consecutive patients undergoing TAVR from October 2014 through December 2019. Based on the iAVA values, patients were placed into categories of no PPM (>0.85 cm 2 /m 2 ), moderate PPM (0.65-0.85 cm 2 /m 2 ), or severe PPM (<0.65 cm 2 /m 2 ). The iAVA and ELI were obtained by iAVA = (AVA/BSA) and ELI = (AVA x ascending aortic area)/((ascending aortic area - AVA) x BSA). We compared the incidence of PPM when using ELI versus iAVA with kappa analysis to verify agreement. Categorical variables were reported as n(%) and continuous variables as mean ± SD. Results: This study included 324 patients. The incidence of severe PPM decreased using iAVA vs. ELI with poor to moderate agreement: no PPM – 73% iAVA vs. 88% ELI (κ = 0.54), moderate PPM – 13% iAVA versus 6.5% ELI (κ < 0), severe PPM – 14% iAVA vs 5.5% ELI (κ = 0.52). Conclusions: Our study concludes that using ELI-based vs iAVA-based definition of PPM decreases the reported incidence and severity of PPM post-TAVR. Abbreviations: AVA: aortic valve area; AoA: ascending aortic area; BEV: balloon-expandable valve; BSA: body surface area; EACVI: European Association of Cardiovascular Imaging; ELI: energy loss index; ELCo: energy loss coefficient: iAVA: indexed aortic valve area; LVOT: left ventricular outflow tract; LVOTD : left ventricular outflow tract diameter; LVOTTVI : LVOT time velocity integral; PPM: Prosthesis-patient mismatch; PLAX: parasternal long axis; SAVR: surgical aortic valve replacement; SEV: self-expanding valve; STJ: sinotubular junction; TAVR: transcatheter aortic valve replacement; Vmax: peak aortic velocity; VTI: time-velocity integral